Sense of Belonging and the Intercultural and Academic Experiences Among International Students at a University in Northern Ireland - Cena, Elida; Burns, Stephanie; Wilson, Paul (Journal of International Students, 2021)
Higher education institutions have a strong interest in attracting international students; however, there is little research on international students’ experience while studying in the UK and how this relates to their adjustment and belonging. This research was conducted with 16 international students at an institution in Northern Ireland, using qualitative interviews to examine academic and sociocultural challenges they experience while studying and living in a new country. Findings suggest that the academic challenges posed by a different educational system, issues affecting social relations within the campus, and living in a homogenous society have an impact on the international student experience. Adjustment challenges were primarily attributable to language and cultural barriers. These findings highlight that it is vital for institutions to better understand students’ needs and tailor their services to enhance international students’ learning experience. The study discusses possible areas for intervention that can be taken into consideration by HEIs.